Keterampilan perawatan dan perbaikan peralatan listrik rumah tangga - Alimuddin Sa’ban Miru (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The main problem in the implementation of community service activities is how to improve the equality of human resources in the rompegading village of Soppeng Regency in maintaining and improving; repairing household electrical appliances. The purpose and benefits of carrying out this activity is to provide basic community knowledge about how to properly maintain and repair household electrical appliances. The rationale behind this training activity is that the people in the Rompegading Soppeng regency no longer have difficulties in maintaining and repairing household electrical appliances. This training was also carried out using the methods of discourse, discussion, question and answer, and simulation (training). It can be concluded that the results of community skills in caring for and repairing household electrical appliances have increased significantly